Odpowiedzi

2010-03-18T15:54:56+01:00
A) 4x-3=3x+5
4x-3x=5-2
x=3

b) 5x +2 =7 - 3x
5x-3x=7-2
2x=5 |:2
x=2,5

c) 3(x-1)=0
3x-3=0
3x=3 |:3
x=1

d)-6(x+1)=24
-6x+6=24
-6x=24-6
-6x=18 |:(-6)
x=(-3)

e) -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-14-1
-10x=-15 |:(-10)
x=1,5

f) 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6-4
-2x=2 |:(-2)
x=(-1)
1 1 1
2010-03-18T16:00:50+01:00
A)
4x-3=3x+5
4x-3x=5+3
x=8
b)
5x +2 =7 - 3x
5x+3x=7-2
8x=5/8
x=5/8
c)
3(x-1)=0
3x-3=0
3x=3/:3
x=1
d)
-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:(-6)
x= -5
e)
-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15 /:(-10)
x=3/2
x=1,5
f)
4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /:(-2)
x=-5
2010-03-18T16:03:46+01:00
A) 4x-3=3x+5 /-3x, +3
4x-3x=5+3
x=8

b) 5x +2 =7 - 3x /+3x,-2
5x+3x= 7-2
8x=5
x=1,6

c) 3(x-1)=0
3x-3=0 /+3
3x=3
x=1

d)-6(x+1)=24
-6x-6=24 /+6
-6x =30 / razy -1
6x= -30
x=0,2

e) -7(x-2)=3x-1
-7x+14=3x-1 /-3x, -14
-10x= -15 /razy -1
10x=15
x= 0(6)7

f) 4(x-1)=6(1+x)
4x-4=6+6x /-6x, +4
-2x=10/ razy -1
2x=-10
x=-0,2